2022
DOI: 10.3390/cancers14122851
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Cancer-Related Fatigue on HRQOL in Survivors of Childhood Cancer: A DCCSS LATER Study

Abstract: Background: Early detection and management of late effects of treatment and their impact on health-related quality of life (HRQOL) has become a key goal of childhood cancer survivorship care. One of the most prevalent late effects is chronic fatigue (CF). The current study aimed to investigate the association between CF and HRQOL in a nationwide cohort of CCS. Methods: Participants were included from the Dutch Childhood Cancer Survivor Study (DCCSS) LATER cohort, a nationwide cohort of CCS. Participants comple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(25 citation statements)
references
References 54 publications
0
25
0
Order By: Relevance
“…The included articles provided data on a total of 14 342 survivors of childhood cancer. Three articles were based on data from a French cohort of survivors of leukaemia, [37][38][39] two articles were from studies in northern Italy, 19,20 two articles were based on data from a Belgian and French cohort of survivors of hematologic cancers 40,41 and five articles used data from the Dutch LATER registry, [21][22][23][24][25] with overlapping populations. All articles were screened for overlapping populations.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The included articles provided data on a total of 14 342 survivors of childhood cancer. Three articles were based on data from a French cohort of survivors of leukaemia, [37][38][39] two articles were from studies in northern Italy, 19,20 two articles were based on data from a Belgian and French cohort of survivors of hematologic cancers 40,41 and five articles used data from the Dutch LATER registry, [21][22][23][24][25] with overlapping populations. All articles were screened for overlapping populations.…”
Section: Resultsmentioning
confidence: 99%
“…31 A study in Norway of 285 survivors of childhood acute lymphoblastic leukaemia and lymphoma found medium-sized differences when comparing scores in survivors with that of the general population on PF (mean, 90.1 vs 94.0, P < .001), BP (mean, 72.2 vs 79.0, P < .001), RP (mean, 75.0 vs 87.4, P < .001) and GH (mean, 64.1 vs 80.1, P < .001). 46 The main mental subdomains found to be coherent with worse QoL were SF 22,25,32,34,35,[37][38][39]46,48,51,52 and MH, 20,25,32,34,35,44,46,49,51 but several studies also found that VT 20,22,25,32,34,35,39,46,52 and RE 25,34,[37][38][39]44,48,52 35 In the five studies that reported comparably better QoL 19,40,42,43,45 among survivors of childhood cancer, both physical and mental scor...…”
Section: Quality Of Lifementioning
confidence: 98%
See 1 more Smart Citation
“…Although effects were mostly small, the consistency of the findings across studies may indicate that these are areas of concern for CCS. The findings may reflect that a substantial proportion of CCS experience physical late effects of cancer and its treatment, among which fatigue is common 36,37 . Also, the findings underline that some CCS may experience impaired HRQOL, and of note, fatigue appeared to be associated with impaired HRQOL in the LATER cohort 37 .…”
Section: Discussionmentioning
confidence: 74%
“…20 The SF-36 is a widely used instrument; several studies used it to determine HRQoL among CCS. 12,[21][22][23][24] The questionnaire includes 36 items covering different aspects of physical and mental health aggregated into eight health domains: physical functioning (PF, 10 items), role-limitations due to physical problems (RP, 4 items), bodily pain (BP, 2 items), general health (GH, 5 items), vitality (VT, 4 items), social functioning (SF, 2 items), role-limitations due to emotional problems (RE, 3 items) and mental health (MH, 5 items). 20,25 These health domains are further collapsed into summary scores that reflect overall physical and mental health: physical component summary (PCS) and mental component summary (MCS).…”
Section: Assessment Of Hrqolmentioning
confidence: 99%